Mini-Review: Can the Metastatic Cascade Be Inhibited by Targeting CD147/EMMPRIN to Prevent Tumor Recurrence? - Rahat, Michal A. (Frontiers in Immunology, 2022)
Solid tumors metastasize very early in their development, and once the metastatic cell is lodged in a remote organ, it can proliferate to generate a metastatic lesion or remain dormant for long periods. Dormant cells represent a real risk for future tumor recurrence, but because they are typically undetectable and insensitive to current modalities of treatment, it is difficult to treat them in time. We describe the metastatic cascade, which is the process that allows tumor cells to detach from the primary tumor, migrate in the tissue, intravasate and extravasate the lymphatics or a blood vessel, adhere to a remote tissue and eventually outgrow. We focus on the critical enabling role of the interactions between tumor cells and immune cells, especially macrophages, in driving the metastatic cascade, and on those stages that can potentially be targeted. In order to prevent the metastatic cascade and tumor recurrence, we would need to target a molecule that is involved in all of the steps of the process, and evidence is brought to suggest that CD147/EMMPRIN is such a protein and that targeting it blocks metastasis and prevents tumor recurrence.